Metaphorical Entailment in BTS Song Lyrics: A Semantic Perspective - Izzet Fikrotul Fauqi; Eva Eva (Proceedings of The ICECRS, 2020)
Language is a means or tool of communication. People have used language as the most common way to communicate with each other. Language is a system of arbitrary vocal symbols by means of which a social group cooperates. When people used language, they bound between one and another, called meaning. The meaning itself sometimes can be interpreted by other people easily, while some of them are not. Metaphorical meaning is the hidden meaning in some literary works, such as song, poem, poetry, and drama, that be able to give a new perspective to the readers or listeners. This research analyse the metaphorical meaning in some of BTS’s song, and its relation to the people who listen to their songs. The objective of this research is to analyze metaphorical entailment in BTS‘s song lyrics through a semantic perspective, and how the metaphorical meaning in BTS’s song in giving new hope to the listener. This research is a Qualitative, specifically descriptive qualitative method. There were two kinds of data in this research to support in analyzing process; the BTS’s song lyrics and interview session. The BTS’s song lyric was from the website, and an interview session was done by two correspondents that passed the criteria.